Problem-Based Learning and Mathematical Creativity in the Perspective of Islamic Education - Ika Yuli Retnawati; Nuni Widiarti; Decky Avrilianda; Ngabiyanto (Attanwir : Jurnal Keislaman dan Pendidikan, 2026)
Problem-Based Learning (PBL) has been increasingly recognized as an effective pedagogical approach in mathematics education, particularly for enhancing students’ critical and creative thinking skills. This study examines the integration of PBL with Islamic educational principles to foster mathematical creativity and character development in students. Using a qualitative theoretical approach and an extensive literature review, the research explores how PBL can be implemented in Islamic-based mathematics education, identifies practical strategies, and addresses challenges such as teacher readiness, infrastructure limitations, and technological integration. Findings indicate that PBL not only deepens students’ conceptual understanding and problem-solving abilities but also promotes moral and spiritual development by embedding Islamic values such as honesty, perseverance, and ethical conduct in learning activities. The study highlights practical implications, including the use of storytelling-based e-comics and AI-supported learning tools, to create a more interactive, contextual, and value-oriented learning environment. Overall, integrating PBL with Islamic education offers a holistic approach that enhances both academic outcomes and character formation in mathematics education.